Is type of work associated with physical activity and sedentary behaviour in women with fibromyalgia? A cross-sectional study from the al-Ándalus project - Maria José Girela-Rejón; Blanca Gavilán-Carrera; Esther Aparicio-Ortega; Milkana Borges-Cosic; Inmaculada C García-Rodríguez; Manuel Delgado-Fernández; Fernando Estévez-López (BMJ Open)
Objectives To analyse the association between the type of work (productive vs reproductive work) and the levels of physical activity and sedentary behaviour in women with fibromyalgia.Method This cross-sectional study involved 258 women with fibromyalgia from southern Spain. Of them, 55% performed reproductive work (unpaid, associated with caregiving and domestic roles) exclusively, while 45% had productive job (remunerated, that results in goods or services). Physical activity of light, moderate and vigorous intensity in the leisure time, at home, at work, and totally were measured through the leisure time physical activity instrument and with the physical activity at home and work instrument, respectively. Sedentary behaviour was measured by the Sedentary Behaviour Questionnaire.Results After adjusting for age, fat percentage, education level and marital status, the multivariate analysis of covariance model informed the existence of significant differences between type of work groups (p<0.001). Women with productive work engaged in more light physical activity at work (mean difference =448.52 min; 95 % CI 179.66 to 717.38; p=0.001), and total physical activity of light (809.72 min; 535.91 to 1085.53; p<0.001) and moderate (299.78 min; 97.31 to 502.25; p=0.004) intensity. Women with reproductive work engaged in more light physical activity at home (379.14; 175.64 to 582.64; p<0.001). Leisure time physical activity and sedentary behaviour were similar in both groups (p>0.05 for all comparisons).Conclusions Women with productive work had greater levels of physical activity compared with those who only did reproductive work, except for physical activity at home. Having productive work might facilitate movement of women with fibromyalgia towards a more active lifestyle.